Analisa Pengaruh Variasi Merek Kampas Rem Tromol Dan Kecepatan Sepeda Motor Honda Supra X125 Terhadap Keausan Kampas Rem - Multazam, Ahmad; Zainuri, Achmad; Sujita, S. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2012)
AbstractBrake is one component of a motor vehicle that serves to slow or stop the study aims to determine the value of the wear of each brand of brake drum caused by variations in the speed of the motorcycle Honda Supra X125 on the braking load 6 kg. Brake that is used in this study there are three variations of the brand is a brand HONDA GENUINE PART, ASPIRA, and KOMACHI with variations at 40, 50 and 60 km / h and braking load 6 kg. The research was conducted in two phases, namely the field of testing and measuring brake wear in the lab. Metrology using a profile projector, in addition to the Rockwell hardness testing is also performed to determine the hardness of each brand of brake lining before and after testing higher speeds with the same braking load time, braking distance and the wear rate also increased.From the research results smallest brake lining wear occurs there at a speed of 40 km / h and braking load 6 kg. Genuine Parts for the Honda brand it wear amounted to 1.574 x 10 -5 mm / sec, while the brand Aspira it wear 8.47 x 10 -5 mm / sec and brands Komachi it wear 3.500 x 10 -5 mm / sec. Largest brake wear occurs at a speed of 60 km / h and braking load 6 kg. Genuine Parts for the Honda brand is equal to 2.373 x 10 -5 mm / sec, while the brand Aspira it wear 3.626 x 10 -5 mm / sec and brands Komachi it wear 3.701 x 10 -5 mm / sec.